PENGARUH KONSEP DIRI DAN KEPERCAYAAN DIRI TERHADAP PRESTASI BELAJAR SISWA SMPN 3 PASAMAN - Sri Wahyuni; M. Arif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The phenomenon that occurs in grade VIII and IX students at SMPN 3 Pasaman. There are several students who have low learning achievement because they are indicated to have a self-concept that is not optimal and are indicated to have low self-confidence. This study aims to: (1) determine how much influence self-concept has on learning achievement (2) how much influence self-confidence has on learning achievement (3) how much influence self-concept and self-confidence have together on learning achievement. This study uses a quantitative approach with an associative type. The population in this study was 164 students. The sampling technique in this study used a stratified random sampling technique, which means taking tiered random samples so that the sampling per class is evenly distributed according to the number of students per class. The sample in this study was 116 samples. The data collection technique used questionnaires and documentation. The instrument used in this study was a self-concept and self-confidence questionnaire developed by the researcher. The data analysis conducted to test the research hypothesis was simple linear regression and multiple linear regression. The results of this study indicate that: (1) there is a positive and significant influence of self-concept (X1) on learning achievement (Y) with a significance value of 0.000 <0.05 and a percentage level of 27.8%. (2) there is a positive and significant influence of the self-confidence variable (X2) on learning achievement (Y) with a significance value of 0.000 <0.05 and a percentage level of 23.6%. (3) there is a significant influence of self-concept (X1) and self-confidence (X2) together on learning achievement with a significance value of 0.000 <0.05 and a percentage level of 37.4%.